Survey for natural Neospora caninum infection in wild and captive birds - Mineo, Tiago W. P. [UNESP]; Carrasco, Adriano O. T. [UNESP]; Raso, Tania F. [UNESP]; Werther, Karin [UNESP]; Pinto, Aramis A. [UNESP]; Machado, Rosangela Z. [UNESP] (Elsevier B.V., 2011)
Neospora caninum is a protozoan parasite that presents worldwide distribution and is mainly implicated as responsible for bovine abortion. Although the presence of birds in cattle-raising properties is positively correlated to higher infection rates, very little has been described about the role of these animals in the parasite's life cycle. In that sense, this work aimed to investigate the serological and histological positivity of different avian species sampled in its natural habitat or in captivity. No serological positivity was observed in the 294 tested serum samples. on the other hand, Apicomplexa-like cysts found in muscular tissues of two Psittaciformes were immunostained with N. caninum antisera. These findings indicate that N. caninum may infect a wider range of hosts than described to date, and that further studies should be performed in order to determine the presence of the infection in different avian species. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Neospora caninum; Psittacine birds; Avian species; Immunohistochemistry; Serology